2016
DOI: 10.1007/s11430-015-0192-1
|View full text |Cite
|
Sign up to set email alerts
|

Improved data gap-filling schemes for estimation of net ecosystem exchange in typical East-Asian croplands

Abstract: The estimation of carbon exchange between ecosystems and the atmosphere suffers unavoidable data gaps in eddy-covariance technique, especially for short-living and fast-growing croplands. In this study we developed a modified gap-filling scheme introducing a leaf area index factor as the vegetation status information based on the conventional light response function for two East-Asian cropland sites (rice and potatoes). This scheme's performance is comparable to the conventional time window scheme, but has the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 41 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…It was reported that 1/r s decreases linearly with log(VPD) for plant species and stomatal sensitivity is proportional to the magnitude of 1/r s at low VPD (≤10 hPa) [49], which was later demonstrated to be consistent with the linear model presented by [50]. High temperature as well as high VPD in the afternoon in dry pre-monsoon season leads to a high evapotranspiration rate and then to a stomatal closure for potato plants in the research region [28]. This regulation could result in a deviation of r s from the estimation by Equations (6) and (7), and consequently the poor efficiency of both the PM-KP approach and the PM-FAO approach in the case of the dry air.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…It was reported that 1/r s decreases linearly with log(VPD) for plant species and stomatal sensitivity is proportional to the magnitude of 1/r s at low VPD (≤10 hPa) [49], which was later demonstrated to be consistent with the linear model presented by [50]. High temperature as well as high VPD in the afternoon in dry pre-monsoon season leads to a high evapotranspiration rate and then to a stomatal closure for potato plants in the research region [28]. This regulation could result in a deviation of r s from the estimation by Equations (6) and (7), and consequently the poor efficiency of both the PM-KP approach and the PM-FAO approach in the case of the dry air.…”
Section: Discussionmentioning
confidence: 54%
“…It was reported that the observed VPD is below the plant physiological threshold (10 hPa) during most of the time of the growing season of rice owing to the permanently flooded terraces with the contribution of intensive precipitation in summer monsoon in the research region [28]. However, the model performance of the PM-KP approach was weak for dry air conditions in the potato field, possibly because of the regulation of leaf water potential by stomata.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Considering the small change rate of chamber air temperature, the deviation in the VPD estimation is slight. As a consequence, the water vapor condensed on the inner wall of the chamber dome gradually, which reduced the solar radiation in the chamber and as a consequence the photosynthesis of the vegetation (Zhao & Lüers, 2016), and thus the net exchange of CO 2 turned from negative (towards the surface) to positive (away from the surface) after t s .…”
Section: Resultsmentioning
confidence: 99%